Analyzing scientific productions and drawing scientific maps related to the medical sciences of Payame Noor University - Mahnaz Mohseni (مجله علم‌سنجی کاسپین)
Background and aim: Payame Noor University of Iran plays an important role in the production of Iranian science in various scientific fields by taking advantage of the existing capacities and conducting various studies. Therefore, the present study deals with scientific productions related to the medical sciences of Payame Noor University. Materials and methods: This descriptive study was conducted with a bibliometric approach. The statistical population of the study included all the scientific documents produced by Payame Noor University in the PubMed medical database until March 27, 2024. To analyze the data and draw scientific maps, the bibliometrics package was used in the R programming language. Findings: A total of 1,947 relevant papers published since 2001 were retrieved. The words "Humans", "Animals", and "Female" are the most important keywords in scientific productions related to medical sciences at Payam Noor University. Chemistry, biology and biochemistry departments of Payam Noor University had the highest number of scientific productions. With 60 articles, betweenness centrality 45.22, closeness centrality 0.0057 and page rank 0.0488, Vesali has been the most prolific author in this field. Statistical analysis has shown that there is a weak correlation between the number of articles and betweenness centrality (p=0.195). Also, there was no significant correlation between the number of articles and closeness centrality (p=0.050). However, there is a significant correlation between the number of articles and page rank (p=0.472). The subject areas of the scientific productions of this university are classified into two main subjects of biomedical studies and studies related to the fields of chemistry and associated factors. Conclusion: Focusing on the fields of chemistry, biology, and biochemistry, Payame Noor University has had the most scientific productions related to medical sciences. Furthermore, the topics of detection limit, spectroscopy, Fourier transform infrared spectroscopy, and hydrogen ion concentration are among the leading topics in the scientific productions of medical sciences at Payam Noor University.